2018
DOI: 10.1111/hepr.13284
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of circular RNAs in hepatic tissue in a model of liver fibrosis and functional analysis of their target genes

Abstract: Aim To measure the expression profile of circular RNA (circRNA) in hepatic tissues in a liver fibrosis model and to explore their function using molecular biology and bioinformatic techniques. Methods The classic CCl4 mouse liver fibrosis model was established alongside a normal control group. The circRNA expression profile of hepatic tissue from the two groups was compared using a high‐throughput circRNA microarray. The differentially expressed circRNAs were identified, and real‐time quantitative polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…As a result, circRNAs are considered to be suitable as biomarkers or prognosis factors in various diseases. The expression pattern of circRNAs in liver fibrosis has been previously reported [14,15]. We found that hsa_circ_0070963 expression was abnormally downregulated in irradiated HSCs.…”
Section: Introductionsupporting
confidence: 71%
“…As a result, circRNAs are considered to be suitable as biomarkers or prognosis factors in various diseases. The expression pattern of circRNAs in liver fibrosis has been previously reported [14,15]. We found that hsa_circ_0070963 expression was abnormally downregulated in irradiated HSCs.…”
Section: Introductionsupporting
confidence: 71%
“…In a model of radiation-induced HSC activation, they found 179 upregulated and 630 downregulated circRNAs compared with quiescent HSCs. In a CCl 4 -induced murine model of hepatic fibrosis, Zhou and colleagues have shown the differential expression of 69 circRNAs, of which 14 were upregulated and 55 downregulated in injured livers in respect to healthy controls [86]. In both experimental settings, bioinformatic analyses indicated that the dysregulated circRNAs may target miRNAs and proteins involved in the activation of HSCs, thus contributing to the development of liver fibrosis [85,86].…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…In a CCl 4 -induced murine model of hepatic fibrosis, Zhou and colleagues have shown the differential expression of 69 circRNAs, of which 14 were upregulated and 55 downregulated in injured livers in respect to healthy controls [86]. In both experimental settings, bioinformatic analyses indicated that the dysregulated circRNAs may target miRNAs and proteins involved in the activation of HSCs, thus contributing to the development of liver fibrosis [85,86]. Among the anti-fibrogenic circRNAs, hsa_circ_0007874 (also known as circ-MTO1) has proved to inhibit HSC activation and liver fibrogenesis by regulating miR-17-5p and Smad7 [87].…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…These differentially expressed circRNAs are involved in the cell composition, biological processes, molecular function, and several cell signal pathways. 34 A novel ligand of CCR2, PC3-secreted microprotein/microseminoprotein (PSMP/MSMP), which can give rise to inflammatory macrophage infiltration and pro-inflammatory cytokines production in HF patients. 35 The antibody of PSMP is a potential therapeutic agent for the treatment of liver fibrosis.…”
Section: Hepatic Fibrosismentioning
confidence: 99%